Splash Page with Music: “Liberdade e controle” - Fragmento 3 by Orquestra Errante - Boer, Sam (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2025)
Every issue of Critical Studies in Improvisation / Études critiques en improvisation opens with a short piece of music related to the issue.For issue 16.1, we're pleased to present the song “Liberdade e controle - Fragmento 3” by Orquestra Errante (used with permission). You can listen to the piece through the button above or via Bandcamp through this link.